2021
DOI: 10.1155/2021/5551338
|View full text |Cite
|
Sign up to set email alerts
|

PPARγ Attenuates Interleukin‐1β‐Induced Cell Apoptosis by Inhibiting NOX2/ROS/p38MAPK Activation in Osteoarthritis Chondrocytes

Abstract: Introduction. Reactive oxygen species (ROS) induced by extracellular cytokines trigger the expression of inflammatory mediators in osteoarthritis (OA) chondrocyte. Peroxisome proliferator-activated receptor gamma (PPARγ) exerts an anti-inflammatory effect. The aim of this study was to elucidate the role of PPARγ in interleukin-1β- (IL-1β-) induced cyclooxygenase-2 (COX-2) and prostaglandin E2 (PGE2) expression through ROS generation in OA chondrocytes. Methods. IL-1β-induced ROS generation and chondrocyte apop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 41 publications
0
14
1
Order By: Relevance
“…This cannot attribute to the inhibition of mitochondria by DPI, for RBCs lack mitochondria. It is hard to explain based on the present data, but it is a common result that DPI cannot inhibit ROS levels to the control group level in many other studies [ 35 , 36 ].…”
Section: Resultscontrasting
confidence: 54%
“…This cannot attribute to the inhibition of mitochondria by DPI, for RBCs lack mitochondria. It is hard to explain based on the present data, but it is a common result that DPI cannot inhibit ROS levels to the control group level in many other studies [ 35 , 36 ].…”
Section: Resultscontrasting
confidence: 54%
“…As a nuclear receptor transcription factor, PPAR γ is involved in the regulation of ROS by regulating redox and biosynthetic processes in mitochondria [ 54 , 55 ]. Activation of PPAR γ inhibited oxidative stress and also negatively regulated the expression of AP-1, NF- κ B, and other inflammatory response genes [ 56 ]. In the present study, PPAR γ was found through the intersection of prediction target genes of vitexin and inflammatory disease-related genes.…”
Section: Discussionmentioning
confidence: 99%
“…NOX4 forms a heterodimer with p22phox without a cytosolic subunit. Several studies have consistently reported the critical roles of NOX2 and NOX4 in OA [ 30 ]. NOX2 is weakly expressed in normal chondrocytes but increases in OA and IL-1β-treated chondrocytes [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%